Prosedur Pemeriksaan Radiografi Cervical Dinamik pada Klinis Herniated Nucleus Pulposus (HNP) di Instalasi Radiologi RSUD Brebes - Putri Apriani; Ari Anggraeni; Ayu Mahanani (Pusat Riset dan Inovasi Nasional, 2025)
Background: Herniated Nucleus Pulposus (HNP) in the cervical region is a condition in which the intervertebral disc protrudes and may compress the nerve roots, causing pain and movement disorders. At the Radiology Department of RSUD Brebes, there are differences in cervical examination techniques compared to standard theory, namely the use of hyperflexion and hyperextension projections. Objective: This study aims to further examine the radiographic techniques used in cervical examinations with clinical indications of Herniated Nucleus Pulposus (HNP), particularly the use of additional lateral hyperflexion and hyperextension projections. Method: This research employed a qualitative method with a case study approach. Data collection was conducted through observation, interviews, documentation, and literature review at the Radiology Department of RSUD Brebes. Informants included five people: three radiographers, one radiology specialist, and one referring physician. Data were analyzed using reduction, presentation, and conclusion drawing techniques. Results: Dynamic cervical radiographic examination for clinical HNP at RSUD Brebes utilized additional hyperflexion and hyperextension projections with the patient standing sideways at the bucky stand, the Central Point (CP) located at cervical 4, and the Central Ray (CR) perpendicular horizontally. Focus Film Distance (FFD) was 100 cm, with exposure factors of 77 kV and 10 mAs. Patient preparation required no special measures, only removing metal objects around the cervical region such as earrings and necklaces. The rationale for using hyperflexion and hyperextension projections in dynamic cervical examinations for HNP cases at RSUD Brebes was to determine whether there was compression or displacement at the intervertebral disc. Conclusion: Dynamic cervical radiographic techniques for HNP cases at RSUD Brebes were conducted using hyperflexion and hyperextension projections. This examination was also used to evaluate degenerative conditions commonly occurring with aging and to assess cervical movement, since this region is more dynamic compared to thoracic and lumbar vertebrae, thus helping identify movement limitations in patients to support diagnosis.